Drying shrinkage characteristics and mechanism primary exploration of MgO-slag mortars. (23rd May 2022) - Ma, Hongqiang; Du, Erxia; Niu, Xiaoyan; Feng, Jingjing
Graphical abstract: Highlights: The maximum drying shrinkage is obtained when the S-MgO content is 15%. The mortar sample mixed with R-MgO shows expansion. The initial and final setting times of the mortar sample mixed with R-MgO are the shortest. Intraparticle porosity, interparticle porosity, and MgO particle size are important factors that affect the drying shrinkage of MgO-slag mortars. By mixing S-MgO + R-MgO or M-MgO + R-MgO, it is possible to prepare building materials with fully compensated drying shrinkage. Abstract: In this work, seven groups of MgO-slag mortars and pastes were prepared with different MgO types and MgO contents. The setting time, compressive strength and drying shrinkage were characterized. The mechanism of drying shrinkage was discussed by means of microscopic test XRD, FT-IR, MIP and SEM-EDS. The results show that the setting time decrease with the increase of MgO activities and contents. The high-activity MgO only shows a higher compressive strength advantage in the early stage, and the higher content of S-MgO, the higher the compressive strength advantage in the later stage. The 120d drying shrinkage first increases and then decreases with the increase of S-MgO contents, and the maximum drying shrinkage is obtained when the S-MgO content is 15%. The drying shrinkage of the mortar mixed with M-MgO is about half of the mortar mixed with S-MgO; the mortar mixed with R-MgO shows expansion change. Intraparticle porosity, interparticle porosity, and MgO particle size are important factors that affect the drying shrinkage of MgO-slag mortars. This study will provide the theoretical basis for the preparation of cementing materials with no length change by using a MgO activator.